Tetra-mu-acetato-kappa O-8:O `-bis[(N-ethylpyrimidin-2-amine)copper(II)](Cu-Cu) - Aiyub, Z.; Badaruddin, E.; Abdullah, Z.; Fairuz, Z.A.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the centrosymmetric title molecule, [Cu-2(CH3COO)(4)-(C6H9N3)(2)], each of the four acetate groups bridges a pair of Cu-II atoms [Cu-Cu = 2.6540 (4) angstrom]. The distorted octahedral geometry of the metal atom is completed by an N-donor atom of the N-ethylpyrimidin-2-amine ligand: an intramolecular N-H center dot center dot center dot O hydrogen links its N-H group to an acetate carboxylate O atom. In the crystal, C-H center dot center dot center dot O interactions link the molecules into a supramolecular chain along the b axis.